The Q-D algorithm for transforming series expansions into a corresponding continued fraction: an extension to cope with zero coefficients - de Andrade, EXL; McCabe, J. H.; Ranga, A. S. (Elsevier B.V., 2003)
An algorithm for deriving a continued fraction that corresponds to two series expansions simultaneously, when there are zero coefficients in one or both series, is given. It is based on using the Q-D algorithm to derive the corresponding fraction for two related series, and then transforming it into the required continued fraction. Two examples are given. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: continued fractions; Pade approximants